Inclusion and behavioural difficulties in secondary schools : representations and practices : a thesis presented for partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, Manawatū, New Zealand - Fortier, Marie-Pierre (Massey University, 2014)
Despite a political commitment towards inclusive education, research evidence suggests that barriers to inclusion in New.Zealand remain. Notably, disciplinary practices exclude students from secondary schools. There is also little evidence as to how teachers define and practice inclusion, in spite of the fact that the translation of inclusion into practice necessitates the development of an articulated and shared vision of what inclusion entails for practice. Thus, this study aims to explore social representations of inclusion among secondary school teachers. It also aims to explore how these representations function in the classroom by examining their relationships with the practices used by teachers to prevent and manage difficult behaviour. The study was designed as an iterative two-phase research process. Phase One involved an online questionnaire intended for teachers, teacher aides, Resource Teachers: Learning and Behaviour and Ministry of Education: Special education staff to explore their representations of inclusion and behavioural difficulties. Building on this preliminary investigation, Phase Two involved case studies conducted with teachers in three schools where multiple sources of information and data collection methods allowed investigation of teachers’ representations and practices in context. Findings indicate that inclusion is multi-dimensional in teachers’ representations with elements pertaining to practices, values, social justice, and resourcing. This reveals that teachers are knowledgeable about inclusion as a professional group. Each school context and teachers’ representations of their school community influenced their respresentations of inclusion. However, results also show that teachers’ representations are anchored in the model of integration as participants name conditions to inclusion, among which is the condition that students’ behavioural needs are not too severe for their presence in regular classrooms. Barriers to inclusion are also identified within teachers’ representations. Teachers’ practices in preventing and dealing with difficult behaviour show a progression with preventative strategies used first and targeted practices used as behaviour seriousness increased. The variety of explanations used by participants to justify their practices point to the importance of understanding the complex relationships between representations and practices to evaluate the inclusiveness of teachers’ actions. Recommendations are made to help individual teachers and school communities building on their existing knowledge for greater inclusion.
Keywords: Inclusive education, New Zealand; Special education, New Zealand; Secondary education, New Zealand; Behaviour of school children; Behavioural problems